Bearing Fault Diagnosis Method Using Envelope Analysis and Euclidean Distance - Haiping Li; Jianmin Zhao; Xinghui Zhang; Hongzhi Teng; Ruifeng Yang; Lishan Hao (Institute of Advanced Engineering and Science, 2014)
Bearings are widely used in rotating machines. Its health status is a significant index to indicate whether machines run continually or not. Detecting the bearing faults timely is very important for the maintenance decision making. In this paper, a new fault diagnosis method based on envelope analysis and Euclidean Distance is developed. Envelope analysis is used to enable the fault frequencies clearly. Then, amplitudes of fault frequencies are used as the fault features. Finally, Euclidean Distance is used to identify the different fault types. This method can identify the fault locations intelligently even if the bearings are under different fault levels. The effectiveness of this methodology is demonstrated using the bearing data sets of Case Western Reserve Univerity. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4186